Greenhouse Gas Mitigation in Forest and Agricultural Lands: Carbon Sequestration - Solomon G. Haile; Clyde W. Fraisse; Vimala D. Nair; Ramachandran P-K Nair (EDIS)
AE435, an 8-page fact sheet by Solomon G. Haile, Clyde W. Fraisse, Vimala D. Nair, and P.K. Ramachandran Nair, addresses some basic questions regarding the prospects of carbon (C) sequestration in forest and agricultural lands and examines the C sequestration potential of different land management practices that could play a role in GHG mitigation strategies. Includes references. Published by the UF Department of Agricultural and Biological Engineering, September 2008.